2020
DOI: 10.1007/s00127-020-01926-5
|View full text |Cite
|
Sign up to set email alerts
|

Childhood maltreatment and poor functional outcomes at the transition to adulthood: a comparison of prospective informant- and retrospective self-reports of maltreatment

Abstract: Purpose Growing evidence suggests that prospective informant-reports and retrospective self-reports of childhood maltreatment may be differentially associated with adult psychopathology. However, it remains unknown how associations for these two maltreatment reporting types compare when considering functional outcomes. The present study compared associations between childhood maltreatment and functional outcomes at age 18 years using these two methods. Methods We used data from the Environmental Risk (E-Risk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 42 publications
(55 reference statements)
0
17
0
Order By: Relevance
“…There were significant positive correlations between the severity of adverse life events experienced in childhood and intrusive reexperiencing in both individuals with ASD and TD subjects in this study. Exposure to traumatic life events in childhood is associated with the appearance of mental illness in adulthood (Latham et al, 2020; McCrory et al, 2017). Previous studies have reported that individuals with maltreatment experience in childhood have an increased risk of PTSD in adulthood (Lu et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…There were significant positive correlations between the severity of adverse life events experienced in childhood and intrusive reexperiencing in both individuals with ASD and TD subjects in this study. Exposure to traumatic life events in childhood is associated with the appearance of mental illness in adulthood (Latham et al, 2020; McCrory et al, 2017). Previous studies have reported that individuals with maltreatment experience in childhood have an increased risk of PTSD in adulthood (Lu et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…One study in 2017 showed that suffering multiple traumas was likely to produce various emotional symptoms, so it is necessary to clarify the difference between a single traumatic incident and multiple traumatic incidents in future studies ( 53 ). Moreover, researchers should combine prospective and retrospective investigations of childhood trauma to better evaluate the impact of childhood trauma ( 54 ).…”
Section: Discussionmentioning
confidence: 99%
“…Third, although all other measures were collected prospectively, exposure to CSA was recorded retrospectively at age 26 years. Research comparing prospective and retrospective reports of childhood maltreatment in the same sample has shown that the two methods identify largely distinct groups of people: a significant proportion of people with prospectively documented evidence of child maltreatment do not later report it, and a significant proportion of those who retrospectively report child maltreatment do not have corroborating prospective records (Baldwin et al, 2019;Danese & Widom, 2020;Latham et al, 2021;Najman et al, 2020). This evidence has led to questions about the veracity of retrospective reports of childhood maltreatment (Widom, 2019), but it is important to note that both prospective and retrospective methods have features that can lead to under-and over-reporting (discussed in Baldwin et al, 2019).…”
Section: Strengths and Limitationsmentioning
confidence: 99%